2021
DOI: 10.3390/rs13142737
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Available Open-Source Remotely Sensed Data in Assessing the Wildfire Ignition and Spread Capacities of Vegetated Surfaces in Romania

Abstract: We bring a practical and comprehensive GIS-based framework to utilize freely available remotely sensed datasets to assess wildfire ignition probability and spreading capacities of vegetated landscapes. The study area consists of the country-level scale of the Romanian territory, characterized by a diversity of vegetated landscapes threatened by climate change. We utilize the Wildfire Ignition Probability/Wildfire Spreading Capacity Index (WIPI/WSCI). WIPI/WSCI models rely on a multi-criteria data mining proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…HH (high-high) cluster townships were distributed in the northwest of Fangshan and central and western Mentougou. (3) The correlation analysis between the spatial pattern of forest landscapes and the forest fire spread hazard showed that the forest fire spread hazard was influenced mainly by landscape diversity (SHDI and PRD), landscape aggregation (AI, CONTAG, and PD), and landscape area (TA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HH (high-high) cluster townships were distributed in the northwest of Fangshan and central and western Mentougou. (3) The correlation analysis between the spatial pattern of forest landscapes and the forest fire spread hazard showed that the forest fire spread hazard was influenced mainly by landscape diversity (SHDI and PRD), landscape aggregation (AI, CONTAG, and PD), and landscape area (TA).…”
Section: Discussionmentioning
confidence: 99%
“…The forest fire spread hazard refers to the possibility of a forest fire spreading (assuming that a forest fire has already begun) [1][2][3][4][5][6]. Under the influence of climate change and land use changes, the occurrence probability and intensity of extreme fires have increased significantly [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Following the hotspot analysis, it was identified that the largest degraded surfaces are the coastal ones (49.80%), followed by the grassland ecosystems In the case of the models that targeted the ecosystems of forests, caves and rivers, lower values were calculated but located above the limit of 0.800, considered a threshold value in order to frame the results in the category of strong and moderate models [74]. However, these values are justified, taking into account the diversity of the causes of degradation as well as their uneven distribution at the national level [75]. The model with a low validation rate was the coastal ecosystems model for which improvements can be made in future studies, aimed at lowering the distinction between the distribution of disturbing factors on land and water and their dispersion with distance from shore [76].…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Europe, the Mediterranean-type climate with the prolonged dry and warm summer period, the flammable vegetation, the complex topography, as well as human activities, favors both the ignition and the spread of wildfires. Furthermore, warmer and drier conditions in the Euro-Mediterranean region are expected over the next decades under future climate projections (Cos et al, 2022;Hysa et al, 2021;Hysa & Spalevic, 2020;Zittis et al, 2019;Nemeth, 2015). Hence, there will be increases in fire extent, intensity and duration of the fire season (Amatulli et al, 2013;Mitsopoulos et al, 2016;Kotroni et al, 2020) leading to an increased likelihood of large wildfires, known as megafires.…”
Section: Introductionmentioning
confidence: 99%